Molecular hydrogen is a potential protective agent in the management of acute lung injury - Yan Zhang; Jin Zhang; Zhiling Fu (BMC, 2022)
Abstract Acute lung injury (ALI) and acute respiratory distress syndrome, which is a more severe form of ALI, are life-threatening clinical syndromes observed in critically ill patients. Treatment methods to alleviate the pathogenesis of ALI have improved to a great extent at present. Although the efficacy of these therapies is limited, their relevance has increased remarkably with the ongoing pandemic caused by the novel coronavirus disease 2019 (COVID-19), which causes severe respiratory distress syndrome. Several studies have demonstrated the preventive and therapeutic effects of molecular hydrogen in the various diseases. The biological effects of molecular hydrogen mainly involve anti-inflammation, antioxidation, and autophagy and cell death modulation. This review focuses on the potential therapeutic effects of molecular hydrogen on ALI and its underlying mechanisms and aims to provide a theoretical basis for the clinical treatment of ALI and COVID-19.